The formalism of the National Jury of Elections to exclude candidates: the case of gifts - German´a Inga, Franco Luis (2024)
In the Peruvian general elections of 2016 and 2021 the Special Electoral Juries and the National Jury of Elections applied article 42 of the Law of Political Organizations, which allows the exclusion of candidates who give or offer gifts to voters during the campaign. The JNE issued 26 resolutions without carrying out a proportionality test in accordance with the American Convention on Human Rights and the jurisprudence of the Inter-American Court of Human Rights. It is concluded that, in the 2016 elections, the JNE violated political rights by issuing four exclusion resolutions, while in the 2021 elections no candidates were excluded for this reason. However, none of the 26 cases should have been initiated, since the exclusion sanctions from the JNE do not conform to the guidelines established by the Inter-American Court in L´opez Mendoza vs. Venezuela and Petro Urrego vs. Colombia. It is recommended that Congress repeal article 42 or that the electoral justice disapply it throughcontrol of conventionality or constitutionality. This would ensure a more democratic electoral process, preservingthe right of candidates to be elected and of citizens to choose.